PROBLEMS OF ENVIRONMENTAL EXPERTOLOGY IN UKRAINE: LEGAL ASPECTS - Zhmur, Nataliia; Budnyk, Olha (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to analyze the problems and gaps of environmental expertise and conduct a comparative analysis with an assessment of the impact on the environment in the legal aspect. Research methods: a combination of general (analysis, synthesis, comparison, induction, deduction) and special research methods (systemic-functional, formal-logical, formal-legal) are applied. Results: environmental impact assessment is a legal tool for preventing harmful environmental consequences, more modern and closer to European standards. Discussion: ensuring the environmental security of the state and direct legal support for the implementation of its environmental policy occupy one of the leading positions. It is indisputable that man together with the surrounding natural environment is a single whole, and most environmental problems are caused by direct or indirect anthropogenic impact on the environment. Conducting environmental assessments as an assessment of the impact on the surrounding natural environment consists, first of all, in the fact that they are, so to speak, the main boundary, the point of control that any planned or ongoing activity must pass, and it can or otherwise harm the environment. With the adoption of the Law of Ukraine «On Environmental Impact Assessment», it introduced a new European model of the environmental impact assessment procedure instead of environmental expertise. This Law made it possible to ensure that Ukraine fulfills a number of other international obligations at an appropriate level. The environmental impact assessment procedure itself is aimed at prevention and prevention of environmental damage, ensuring environmental safety, environmental protection, rational use and reproduction of natural resources, in the process of decision-making on the implementation of economic activities that may have a significant impact on the environment, taking into account state, public and private interests.